2018
DOI: 10.1029/2018sw002034
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Ionospheric Specifications During Geomagnetic Storms: TEC and foF2 During the 2013 March Storm Event

Abstract: To address challenges of assessing space weather modeling capabilities, the Community Coordinated Modeling Center is leading a newly established International Forum for Space Weather Modeling Capabilities Assessment. This paper presents preliminary results of validation of modeled foF2 (F 2 layer critical frequency) and TEC (total electron content) during the first selected 2013 March storm event (17 March 2013). In this study, we used eight ionospheric models ranging from empirical to physics-based, coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 60 publications
3
67
1
Order By: Relevance
“…First, it may support the operations that are based on long‐term ionospheric forecasting (e.g., long‐term planning purposes for HF communication/broadcasting applications). In addition, it was found to be crucial for the fair evaluation of the modeling capabilities in predicting the short‐term impact of space weather on the near‐Earth's space environment (e.g., Burns et al, ; Shim et al, ). Finally, it supports the effective assessment of prediction abilities with respect to emerging trends in I/T climatology (e.g., long‐term trends and different variability in different solar cycles) that may be considered as key drivers for the development of new and/or updated models.…”
Section: Introductionmentioning
confidence: 99%
“…First, it may support the operations that are based on long‐term ionospheric forecasting (e.g., long‐term planning purposes for HF communication/broadcasting applications). In addition, it was found to be crucial for the fair evaluation of the modeling capabilities in predicting the short‐term impact of space weather on the near‐Earth's space environment (e.g., Burns et al, ; Shim et al, ). Finally, it supports the effective assessment of prediction abilities with respect to emerging trends in I/T climatology (e.g., long‐term trends and different variability in different solar cycles) that may be considered as key drivers for the development of new and/or updated models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhu et al (2017) shows that a better low and middle latitude electrodynamic solver for GITM would improve the modeled zonal electric field and thus the EIA morphology. On a side note, discrepancies between simulated EIAs from various models, GITM and TIE-GCM included, have been shown by Fang et al (2014) for a geomagnetically quiet day and by Shim et al (2018) for a geomagnetic storm. Both studies attribute the cause of the discrepancies to the different lower boundary forcings and electric fields in different models.…”
Section: Discussionmentioning
confidence: 99%
“…below the G1 level of minor geomagnetic disturbance activity), it needs to be noted that the selection of geomagnetic quiet periods as well as the definition of quiet times can be challenging and generally depends on the time constants of the phenomena under consideration. For example, Shim et al () used as a quiet time reference a 30‐day median value at a given time where the 30 days consist of 15 days before and 15 days after a storm. Kalafatoglu Eyigüler et al (), on the other hand, determined the quiet time interval by inspecting the Challenging Minisatellite Payload (CHAMP) neutral density variations on the day preceding the geomagnetic storm.…”
Section: Selection Of Time Intervals/eventsmentioning
confidence: 99%
“…Shim et al () assessed how well the ionospheric models predict storm time f o F 2 and TEC by considering quantities, such as TEC and f o F 2 changes and percentage changes compared to quiet time background, at 12 selected midlatitude locations in the American and European‐African longitude sectors. They found that the performance of the model varies with locations, even within a localized region like Europe, as well as with the metrics considered.…”
Section: Selection Of Validation Data Setsmentioning
confidence: 99%